The role of single fraction Gamma Knife radiosurgery for intraventricular central neurocytomas and the utility of F-18 fluroethyltyrosine: two case reports - Michaela Dedeciusova; John O. Prior; Luis Schiappacasse; David Patin; Marc Levivier; Constantin Tuleasca (Journal of Medical Case Reports, 2022)
Abstract Background Primary treatment of central neurocytomas is surgical resection. Gamma Knife surgery is considered a valuable therapeutic option in case of residual (after subtotal resection) or recurrent central neurocytomas. Here, we focused on the role of F-18 fluroethyltyrosine as a marker to document tumor progression after initial resection, in the context of an atypical central neurocytoma. We also describe MIB-1’s role in evaluating therapeutic decision-making. Case presentation Two patients with central neurocytomas were treated by Gamma Knife surgery in our center. The first case (31-year-old Caucasian male) had atypical central neurocytoma. Four and a half years after surgical resection, magnetic resonance imaging and F-18 fluroethyltyrosine documented clear progression of residual central neurocytoma, further treated by Gamma Knife surgery (18 Gy at 50%, target volume 1.4 cc, and prescription isodose volume 1.8 cc). The initial post-Gamma Knife surgery clinical course was uneventful, with progressive volumetric reduction of residual tumor up to 4.5 years, when out-of-field recurrence was suspected and confirmed by local F-18 fluroethyltyrosine hyperactivity. Second single-fraction Gamma Knife surgery was performed (18 Gy at 50%, target volume 0.49 cc, prescription isodose volume 0.72 cc). The second (32-year-old Caucasian female) had previous subtotal resection and typical central neurocytoma. Seven years later, she had residual tumor progression. Single-fraction Gamma Knife surgery was performed (16 Gy at 50% isodose line, target volume 1.7 cc, and prescription isodose volume 2.5 cc). Last follow-up showed tumor volume reduction. Follow-up magnetic resonance imaging showed important volumetric reduction of both treated lesions. Conclusions In atypical central neurocytomas, F-18 fluroethyltyrosine could be used as postoperative examination to detect small tumor remnants, follow-up evaluation following the Gamma Knife surgery or, in select cases, following surgical resection. The role of MIB-1 is important in therapeutic decision-making, as tumors with MIB-1 exceeding 2% are characterized by more aggressive clinical course. Single-fraction Gamma Knife surgery remains a valuable therapeutic option for postoperative residual atypical central neurocytomas and central neurocytoma recurrences.